Lepidochitona bullocki, una nueva especie de quitón (Polyplacophora: Ischnochitonidae) del Caribe colombiano - I. García-Ríos, Cedar (Universidad de Costa Rica, 2011)
The genus Lepidochitona is one of the most diverse in the Southern Caribbean. In order to describe this new species, twenty specimens of L. bullocki sp. nov. were collected by hand on the rocky coast, from 0.25 to 1.5m depth, and a shore distance of 1 to 5m, between the Northern section of Rodadero beach and Puerto Luz, in Santa Marta, Colombia. The specimens were small, with maximum observed size of 7.3mm. This is the fourth species of the genus Lepidochitona described for the Caribbean. The previously known species were L. liozonis (Dall y Simpson 1901), L. rosea (Kaas 1972) and L. rufoi (García-Ríos 2010). L. bullocki differs from L. liozonis and L. rosea in having a rough tegmentum and color. It differs from L. rufoi in having longer and numerous hyaline spicules, bigger size and broader central radula tooth. Lepidochitona bullocki is the only Caribbean species of the genus frequently located on the illuminated side of rocks in the shallow sublitoral zone.